Source Variation in Fruit, Seed Germination and Seedling Characteristics of Diploknema butyracea (Roxb.) H.J. Lam - Bahar, Nawa (Indian Forester, 2019)
Diploknema butyracea is a fast growing species and known for the yield of edible oil from kernels. Studies on source variation for quality seedling production undertaken on fifteen seed sources sampled from different locations in Uttarakhand. Variation for most of the studied characters showed that non-clinal. The population of Harkate was found to be the best on the basis of weight, germination per cent and vigour index of seed as an important criterion for delineation the superior seed source. This preliminary investigation will pave the way for further improvement of the species for better productivity.